ANALISIS TEOLOGIS KONSEP KESELAMATAN DITINJAU DARI SEGI MATI SYAHID DAN BUNUH DIRI MENURUT PERSPEKTIF RASUL PAULUS - Yorande Tumaang; Kristi, Perianto Buluara Pasonda, Ira Alfa Toratu (ADISAM PUBLISHER, 2026)
This writing is a theological analysis of martyrdom and suicide. With the aim that this writing can add insight into the theology of youth as the next generation of the Church with regard to understanding the concept of salvation in terms of martyrdom and killing and strengthening a young man's faith in Jesus Christ who is Lord and Savior. This writing is based on observation because many people do not understand the concept of salvation from martyrdom and death by suicide. Many people think that when someone commits suicide they will get salvation like when they die as a martyr. With suicide will end the problems faced so that one's mind is no longer tormented. Based on this assumption, the authors are interested in analyzing the topic above by using a qualitative approach and focusing on data or information from the Bible as the main literature and other literature obtained that provides information about the concept of salvation when someone dies as a martyr by committing suicide.